Effective Classroom Management Strategies to Improve Student Discipline and Engagement in Islamic Education Lessons at SDN 32 Rejang Lebong - Yessy Rahmaniar; Idi Warsah; Dewi Purnama Sari (Indonesian Journal for Islamic Studies, 2023)
Classroom management is an effort made by the teacher, including planning, organizing the class so that optimal conditions are created and maintained for the teaching and learning process in the classroom, which includes structuring students and existing facilities. This research intends to explore and assess effective classroom management practices that can increase student discipline and involvement in Islamic Religious Education (PAI) courses at State Elementary School (SDN) 32 Rejang Lebong. Using techniques from observation, interviews, and document analysis, the research methodology is qualitative. SDN 32 Rejang Lebong students and PAI teachers made up the research respondents. The research results show that implementing effective classroom management strategies, including interactive-based learning, use of technology, and providing positive feedback, has a positive impact on improving student discipline. Apart from that, this strategy also increases student involvement in PAI learning, creating a positive and dynamic learning environment. The implications of this study include recommendations for PAI teachers to pay more attention to aspects of classroom management that create a positive atmosphere and encourage student involvement in learning.